Analisis Faktor-Faktor Yang Mempengaruhi Struktur Modal Pada Bank Syariah Tahun 2011-2013 - Fatmawati, Indah; , Dra. Wafiatun Mukharomah, M.M (2015)
This research purposes to know ability what is asset structure, growth, and profitability, size and business risk significance to capital structure at Syariah Banks in Indonesia. The research result expects to be consideration to making decision in financial policy so it can optimal of capital structure and firm value. This research uses 10 Syariah Banks to sample listed in Indonesia and chooses with purposive sampling. Data of this research uses financial report each banks to be sample with period 2011 - 2013. Independent variable of this research is asset structure, growth, profitability, size and business risk; and dependent variable of this research is capital structure. Analysis uses regression linier, coefficient determination (R²) and hypothesis test with t and F test. Partial test result shows asset structure influence significance to capital structure. While growth, profitability, size and business risk are not significance to capital structure. Simultaneous test asset structure, growth, profitability, size and business risk variables are not influence and significance to capital structure